Shelf-life and quality of guava (Psidium guajava) affected by chitosan based coating - SRIVASTAVA, ANURADHA; SIDDIQUI, S; ATTRI, B L (The Indian Journal of Agricultural Sciences, 2019)
The present study was carried out during 2013–14 to evaluate the effect of 1% chitosan + 2% calcium gluconate as texture enhancer + 0.2% tocopherol as antioxidant + 100 ppm kinetin as antisenescent + 1.5% tulsi as antimicrobial agent on shelf-life of guava fruits under room temperature (RT) (33±3ºC, 80±5% RH) and low temperature (LT) (i.e. 10±1ºC, 55±5% RH) storage conditions. This coating significantly reduced the weight loss, rate of ripening, decay loss, respiration rate, ethylene evolution and accumulation of total sugars in guava fruits both at RT and LT storage. Coated fruits retained firmness (9.3 kg/cm2, 12.2 kg/cm2), total soluble solids (10.7%, 10.0%), acidity (0.474%, 0.487%), ascorbic acid (124.8 mg/100g, 107.8 mg/100g), phenols (3.57 mg/g, 3.36 mg/g), pectin (0.71%, 0.69%), total chlorophyll (1.18 mg/100mm2, 1.15mg/100mm2) and total carotenoids (0.22 mg/100mm2, 0.208 mg/100mm2) significantly better than uncoated fruits both at RT and LT storage, respectively. This chitosan based functional edible coating enhanced the shelf-life of guava up to 8 and 20 days at RT and LT conditions, respectively as against 4 and 12 days for uncoated fruits at the respective storage conditions.